Benefits of pectin coating cuticle damaged egg to prevent contamination with S. enteritidis and E. coli during sanitization with slightly acidic electrolyzed water - Talaat Alshrief, Lamiaa M.; Gamal, Ayat M.; Heneter, Asmaa M. (Journal of Advanced Veterinary Research, 2025)
Ensuring the microbial safety of eggs is essential to reduce foodborne illnesses caused by Escherichia coli and Salmonella enteritidis. This study aimed to evaluate the efficacy of slightly acidic electrolyzed water (SAEW) and SAEW combined with pectin coating (SAEW-p) in reducing bacterial survival on eggshells and egg contents during refrigerated storage over 7 days. Fresh cuticle-damaged eggs were artificially inoculated with E. coli and S. enteritidis and subjected to SAEW or SAEW-p treatments. Bacterial counts were assessed on day 0 and throughout storage (days 1, 3, 5, and 7) at 4°C. On eggshells, SAEW-p treatment demonstrated significantly enhanced bacterial reduction compared to SAEW alone. By day 7, SAEW-p reduced E. coli and S. enteritidis counts to 3.30 and 3.74 log CFU/ml, respectively, compared to 4.67 and 4.38 log CFU/ml for SAEW-treated eggs and 5.65 and 5.37 log CFU/ml for the control. In egg contents, SAEW-p eliminated E. coli by day 5 and maintained sterility through day 7, whereas SAEW alone achieved partial bacterial reduction. The superior efficacy of SAEW-p is attributed to the synergistic effect of SAEW’s oxidative disinfection and the physical barrier provided by the pectin coating, which inhibited bacterial recontamination and moisture loss. These findings highlight the potential of SAEW-p as a safe, eco-friendly, and highly effective treatment to enhance microbial safety and extend the shelf life of eggs during storage. The combined approach offers a promising solution for the food industry to mitigate contamination risks and ensure food safety.